Assessment of the Total Effective Dose to the Representative Person in Greece, after a Hypothetical Release from a Nuclear Power Plant - Salpadimos, Nikos; Karfopoulos, Konstantinos; Seimenis, Ioannis; Potiriadis, Constantinos (HNPS Advances in Nuclear Physics, 2025)
The Greek Atomic Energy Commission (EEAE), as the national regulatory authority, is responsible for ensuring radiological protection and nuclear safety. To this end, EEAE focuses on the assessment of nuclear or radiological emergencies, which may entail radiological risk for the country. As part of the risk assessment studies conducted by EEAE, a total of 40 worst-case release scenarios from a neighboring nuclear power plant were identified and studied in depth, using atmospheric dispersion software Hysplit and decision support system JRodos. This work focuses on further analyzing the consequences of these release scenarios, by calculating the total effective dose to the representative person. The representative person is defined as a hypothetical individual, located in the areas within Greece that exhibit the highest radionuclide deposition and dose rates, and engaged to activities leading to potential exposure. The main exposure pathways were identified, while agricultural and livestock data provided by the Hellenic Statistical Authority were incorporated into the analysis. The total effective dose was calculated by applying appropriate dose coefficients. The results were compared to the dose limits which are defined in the Greek legislation. The analysis concluded that, even for the critical groups of the population, the calculated dose remained below the established limits. It was also evident that compliance with recommended countermeasures would significantly reduce the total effective dose, further enhancing public safety. This work focuses on further analyzing the consequences of these release scenarios, by calculating the total effective dose to the representative person. The representative person is defined as a hypothetical individual, located in the areas within Greece that exhibit the highest radionuclide deposition and dose rates, and engaged to activities leading to potential exposure. The main exposure pathways were identified, while agricultural and livestock data provided by the Hellenic Statistical Authority were incorporated into the analysis. The total effective dose was calculated by applying appropriate dose coefficients (3). The results were compared to the dose limits which are defined in the Greek legislation (4). The analysis concluded that, even for the critical groups of the population, the calculated dose remained below the established limits. It was also evident, that compliance with recommended countermeasures would significantly reduce the total effective dose, further enhancing public safety.